Mafhūm Trisakti libinā'i al-Balad al-Maśāli min Manẓūri al-Qur'ān: Iktishāf Jawānib Trisakti min Kutub al-Tafāsīr al-Jāwiyyah - Ali Fahrudin; Umar Alfaruq (Center for Research and Development of Religious Literature and Heritage, 2023)
Trisakti was one of Sukarno's ideas for realizing nationalism at the policy level, although during his reign this idea was not fully realized. Sukarno revealed his Trisakti concept when he addressed the Fourth General Session of the MPRS on June 22, 1966. Trisakti contains three political ideals to uphold nationalism in Indonesia, namely: sovereignty and freedom in politics, personality in culture, and independence in the economy. This concept began to be carried forward in the era of Jokowi's leadership as the 7th President. To reexamine this idea, the author tries to elaborate on it one by one in the view of the Qur'an, using a thematic method by taking sources from the interpretations of Javanese mufassir. This is because their interpretation of the Quran is closer to Sukarno's culture whose background is the same as Javanese. The conclusion of this discussion is that the Javanese mufassir agreed with Sukarno's ideas because none of the Trisakti concepts violated religious rules. This can be revealed from the source of Qur'anic verses related to the concept of Trisakti, both explicitly and implicitly, as implied in the story of Prophet Sulayman about political sovereignty and the story of Prophet Yusuf about economic independence.